EEG profiles during general anesthesia in children: A comparative study between sevoflurane and propofol. Issue 3 (12th February 2019) - Rigouzzo, Agnes; Khoy‐Ear, Linda; Laude, Dominique; Louvet, Nicolas; Moutard, Marie‐Laure; Sabourdin, Nada; Constant, Isabelle
Abstract: Background: In this prospective study, we describe the electroencephalographic (EEG) profiles in children anesthetized with sevoflurane or propofol. Methods: Seventy‐three subjects (11 years, range 5‐18) were included and randomly assigned to two groups according to the anesthetic agent. Anesthesia was performed by target‐controlled infusion of propofol (group P) or by sevoflurane inhalation (group S). Steady‐state periods were performed at a fixed randomized concentration between 2, 3, 4, 5, and 6 μg.ml −1 of propofol in group P and between 1, 2, 3, 4, and 5% of sevoflurane in group S. Remifentanil was continuously administered throughout the study. Clinical data, Bispectral Index (BIS), and raw EEG were continuously recorded. The relationship between BIS and anesthetic concentrations was studied using nonlinear regression. For all steady‐state periods, EEG traces were reviewed to assess the presence of epileptoid signs, and spectral analysis of raw EEG was performed. Results: Under propofol, BIS decreased monotonically and EEG slowed down as concentrations increased from 2 to 6 μg.ml −1 . Under sevoflurane, BIS decreased from 0% to 4% and paradoxically rose from 4% to 5% of expired concentration: this increase in BIS was associated with the occurrence of fast oscillations and epileptoid signs on the EEG trace. Propofol was associated with more delta waves and burst suppression periods compared to sevoflurane. Conclusion: Under deep anesthesia, the BIS and electroencephalographic profiles differ between propofol and sevoflurane. For high concentrations of sevoflurane, an elevated BIS value may be interpreted as a sign of epileptoid patterns or EEG fast oscillations rather than an insufficient depth of hypnosis.